CYTOARCHITECTURE CHARACTERIZATIONOF FOETAL SPLEENINTHE ALPACA(LAMAPACOS) - Arias M., Walter (2011)
The aim of the present study was to determine the spleen cytoarchitecture in alpacafetuses of different stages of development. Sixteen alpaca fetuses were obtained fromfemale alpacas slaughtered in the central highlands of Peru. The fetuses were distributedin six groups according to their fetal age (55, 100, 120, 150, 180, and 200 days). Spleens were dissected and samples were stained with hematoxylin-eosin (cellular distribution),Masson ́s trichrome (collagen and muscle fibers), and periodic acid Schiff for argenticimpregnation (reticular fibers) for histological evaluation. Macroscopically, the spleen at55 days of age is slightly outlined, at 120 days is lobed with a triangular shape and at 150days had the appearance of the mature animal. Microscopically, at 55 days there is apredominance of transitional embryonic connective tissue to reticular tissue and somelymphoid cells are located in large vessels, plus cells compatible with hematopoieticneststhat are seen in all later stages. At day 100, fibrous connective tissue of the capsuleinfiltrates the parenchymato form trabecules and lymphoid cells form lymphoid cumulithat surround the large vessels. At day 120, lymphoid cumuli can be named as white pulp,and the hematopoietic nests become the erythroid series by day 150. At 180 days, lymphoidfollicles are filled with lymphocytes resembling mature lymphoid follicles, where thecentral arteriole is displaced to the surface. Finally, by day 200, the spleen has similarhistological appearance of the adult.